Новые виды мух-пестрокрылок рода Urophora (Diptera, Tephritidae) из Таджикистана - Корнеев, В.А. (Вестник зоологии, 1984)
New Species of the Urophora Fruit Fly Genus (Diptera, Tephritidae) from Tadjikistan. Korneyey V. A. — Vestn. zool., 1984, No. 1. Urophora solaris sp. n. differs from all other Palearctic species by high cheeks, yellow mesonotum with brown stripes and spots and by unusual wing patlern. Type-material: holotype female, Tadjik SSR, Khorog. Urophora stalker sp. n.— similar to U. solstitialis L., U. kazachstanica V. Richter and U. affinis Frauen feld, differs from them by the presence of subbasal belt, wide yellow stripe on thorax sides; vien R₁, joints C at the wing's centre. Type-ma terial: holotype female, Tadjik SSR, Kulyab region, Muminabad.